Local tetanus: A case report - B C Ibe; G N Adimora; S O Iloeje (International Journal of Medicine and Health Development, 1999)
A case of local tetanus in a 3 year old male child is reported. It involved the left lower limb and was characterised by rigidity and provocative spasms of the affected limb. The suspected portal of entry was through an intramuscular injection given in the left buttock 13 days prior to the onset of symptoms. The child contracted tetanus despite receiving 3 doses of DPT during infancy. To obviate such possible cases of vaccine failure, the reintroduction of booster doses of vaccine in the routine immunisation schedule is suggested.